1992
DOI: 10.1111/j.1469-7998.1992.tb04340.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation and phylogenetic relationships of Jasus spp. (Decapoda: Palinuridae)

Abstract: The seven species of rock lobster in the genus Jasus have a fragmented circumpolar distribution, inhabiting continental or island waters of the Southern Ocean. Gene flow between nominal species is possible as the planktonic larval stages of Jasus are widely dispersed in major oceanic gyres. Restriction endonuclease analysis of mitochondrial DNA (mtDNA) from five species (J. verreauxi, J. novaehollandiae, J. edwardsii, J. lalandii and J. tristani) was used to assess taxa previously defined only by morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In Jasus edwardsii, OVENDEN et al (1992) have compared 13 populations and obtained a nucleotides substitution mean of about 0.78 whereas the heterozygosity was low in this same species (0.015 according to SMITH ef al., 1980). BRASHER et al (1992b) confirmed a high level of mitochondrial polymorphism in the genus Jasus by studying 5 species. Seeing that OVENDEN (1990) specified that some marine species have less variable mitochondrial génomes than previously studied terrestrial and freshwater species, we can hope that mitochondrial DNA will be a suitable molecular marker in crayfish.…”
Section: Introductionsupporting
confidence: 54%
“…In Jasus edwardsii, OVENDEN et al (1992) have compared 13 populations and obtained a nucleotides substitution mean of about 0.78 whereas the heterozygosity was low in this same species (0.015 according to SMITH ef al., 1980). BRASHER et al (1992b) confirmed a high level of mitochondrial polymorphism in the genus Jasus by studying 5 species. Seeing that OVENDEN (1990) specified that some marine species have less variable mitochondrial génomes than previously studied terrestrial and freshwater species, we can hope that mitochondrial DNA will be a suitable molecular marker in crayfish.…”
Section: Introductionsupporting
confidence: 54%
“…In addition, the marker 12S presented divergences approximately of 6.5% and 7.5 %, with the species H. canci and H. japonica, respectively, being within the expected values for barnacle species within the same genus (Chan et al 2007(Chan et al , 2009). The marker 16S also showed 7 % of genetic divergence with the only specimen of Heteralepas (unidentified) available in public databases (Schiffer & Herbig 2016, GenBank accession KT947465), which is in accordance with the results obtained for other crustaceans (Brasher et al 1992;Machado et al 1993). H. adiposa Zevina, 1982 andH.…”
Section: Discussionsupporting
confidence: 74%
“…We suggest that the evolutionary biology of G. maculatus parallels that of species that have long‐duration planktonic marine larval stages (e.g. Brasher et al . 1992; Ovenden et al .…”
Section: Discussionmentioning
confidence: 79%